Focal mechanism and stress field in the northeastern Tibetan Plateau: insight into layered crustal deformations. Issue 3 (14th June 2019) - Han, Cunrui; Huang, Zhouchuan; Xu, Mingjie; Wang, Liangshu; Mi, Ning; Yu, Dayong; Li, Hua
SUMMARY: Focal mechanism solutions (FMSs) reflect the stress field underground directly. They provide essential clue for crustal deformations and therefore improve our understanding of tectonic uplift and expansion of the Tibetan Plateau. In this study, we applied generalized Cut and Paste and P -wave first-motion methods to determine 334 FMSs (2.0 ≤ M w ≤ 6.4) with the data recorded by a new temporary network deployed in the NE Tibetan Plateau by ChinArray project. We then used 1015 FMSs (including 681 published FMSs) to calculate the regional stress field with a damped linear inversion. The results suggest dominant thrust and strike-slip faulting environments in the NE Tibetan Plateau. From the Qilian thrust belt to the Qinling orogen, the maximum horizontal stress orientations (${S_ H}$ ) rotate clockwise from NNE to NE, and further to EW, showing a fan-shaped pattern. The derived minimum horizontal stress orientations (${S_ h}$ ) are parallel to the aligned fabrics in the mantle lithosphere indicated by shear wave splitting measurements, suggesting vertically coherent deformation in the NE Tibetan Plateau. Beneath the SW Qinling adjacent to the plateau, however, the stress orientations in the shallow and deep crust are different, whereas the deep crustal stress field indicates possible ductile crustal flow or shear.